The case for internal communication: an investigation into consortia forming. (13th January 2021) - Lemon, Laura L.; Towery, Nathan A.
Abstract : Purpose: The present study investigates the nature of newly formed organizations and how internal communication influences these entities, where change is inherent. Organizational life for government contractors is unusual in that employees experience routine changes to upper management, company values, goals and objectives every few years, which leads to the creation of a new consortium that is loosely coupled. Such research provides insight beyond the single-entity organization, which tends to dominate most public relations and internal communication literature. Design/methodology/approach: Given the lack of research exploring consortia and internal communication to get beyond the homogeneous organization, an in-depth case study methodology was the most appropriate approach. A multi-site government contractor was chosen as the research site, relying on interviews and focus groups ( n  = 77) to collect data. Findings: Effective internal communication practices are even more important for consortia, like government contractors, since employees of these organizations are guaranteed to experience frequent change. Therefore, communicating to the unknown audience, building trust in the absence of a prior connection, and preparing for the unintended consequences are imperative to navigating the complexity surrounding consortia forming and cultivating employee buy-in. Originality/value: This study presents new, transferable knowledge of internal communication during consortia forming, where to be successful, internal communication needs anticipate the unintended consequences and develop a strategy around the uncertainty. Such strategy is about welcoming diverse voices and actively listening to their preferred needs. In addition, a definition of the unknown audience is provided.